HIV infection is independently associated with a higher concentration of alpha‐1 antitrypsin. Issue 10 (30th August 2018) - Thudium, RF; Lundgren, J; Benfield, T; Nordestgaard, BG; Borges, ÁH; Gerstoft, J; Nielsen, SD; Ronit, A; ,
Abstract : Objectives: Alpha‐1 antitrypsin (AAT) deficiency is associated with an increased risk of chronic obstructive pulmonary disease and has been related to CD4 T‐cell count decline in people living with HIV (PLWH). We determined whether HIV status is associated with AAT concentrations and assessed associations between AAT concentration, pulmonary function and immunological status. Methods: Alpha‐1 antitrypsin was measured and spirometry performed in 1011 PLWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) study and in 11 962 age‐ and sex‐matched uninfected controls. We studied associations between AAT concentration, HIV status, pulmonary function, and current and nadir CD4 T‐cell counts using multivariate linear regression analyses. Results: The mean age of PLWH was 50.7 [standard deviation (SD) 11.3] years and 98.6% were receiving combination antiretroviral therapy (cART). The mean current CD4 T‐cell count was 718 (SD 284) cells/μL. PLWH had a higher median AAT concentration than uninfected controls [1.4 (interquartile range (IQR) 1.3–1.6) versus 1.3 (IQR 1.2–1.4) g/L; P < 0.0001] and HIV infection was independently associated with higher AAT concentration [adjusted β = 0.10 g/L; 95% confidence interval (CI) 0.08; 0.11 g/L; P < 0.001]. Low AAT concentration (< 1.0 g/L) was not more common in PLWH with airflow limitation (defined as forced expiratory volume in 1 second/forced vital capacity (FEV1 /FVC) < 0.7 with FEV1 ‐predicted < 80%) compared with uninfected controls with airflow limitation, and the effect of AAT on FEV1 %‐predicted was comparable to that in uninfected controls ( P ‐interaction = 0.66). AAT concentration was not associated with current or nadir CD4 T‐cell count. Conclusions: HIV infection was independently associated with a higher concentration of AAT through unknown mechanisms. However, AAT does not seem to contribute to lower pulmonary function or to low CD4 T‐cell counts in PLWH.